Death of a gentle lady - Beaton, M. C. (New York : Warner Books, 2008)
"Scotland$1 (Bs most laconic and low-tech policeman, Hamish MacBeth, is back and this time he must investigate the death of a gentle lady"--Provided by the publisher.s
Keywords: MacBeth, Hamish (Fictitious character) -- Fiction; Police -- Scotland -- Highlands -- Fiction; Highlands (Scotland) -- Fiction; Mystery fiction